Comparación de la metodología BIM 5D vs la tradicional en las fases de planificación y diseño. Caso de estudio: Laboratorios de Diseño Gráfico-ESPOCH. - Peña Guijarro, Ronny Iván (2024)
The objective of this research was to compare the 5D BIM methodology with the traditional one in the planning and design phases of a case study, in order to determine their differences in terms of quantification of work quantities, deadline and budget. This research was of an applied, nonexperimental type, with a descriptive-correlational scope and a mixed approach. For this, the information developed by the traditional methodology of the “Laboratorios de Diseño Gráfico-ESPOCH” project was compiled, based on 152 items. Then, the BIM methodology was developed for the project, extracting quantities, work scheduling and estimating the budget for comparison. This showed that in 58% of items there were variations in the calculation with BIM, caused by the control and precision in the model. The deadline presented a variation of 30 additional days with BIM, understanding that the project will not be fulfilled within the initially scheduled deadline. In the budget there was an overestimation of 0.20% of the traditional methodology, however, all subchapters presented considerable variations, directly affecting the investment strategies in the execution. Despite not having a local implementation guide, BIM offered advantages such as: having a centralized model, precision in the quantification of the work, incorporation of the deadline and budget to the three dimensional model, having a simulation of the 5D BIM construction process, characteristics that the traditional methodology does not offer.